Encyclopedia of Microfluidics and Nanofluidics - Li, Dongqing; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Covering all aspects of transport phenomena on the nano- and micro-scale, Springer$1 (Bs Encyclopedia of Microfluidics and Nanofluidics includes over 750 entries in three alphabetically-arranged volumes including the most up-to-date research, insights, and applied techniques across all areas. Specifically, subjects covered in this comprehensive Springer Reference include electrical double-layers, optofluidics, DNC lab-on-a-chip, nanosensors, and more. Please note that this publication is available as print only OR online only OR print + online set. Save 75% of the online list price when purchasing the bundle.s
A selection of entries in this reference include: Electrical double layers -- Electro osmosis -- Electrophoresis -- Dielectrophoresis -- Quantum dots -- Electrowetting -- Theoretical models and numerical simulations (e.g., continuum and MDS) -- Pressure-driven single phase liquid flows -- Pressure-driven single phase gas flows -- Pressure-driven two phase flows -- Electroosmotic flow -- Electrophoretic motion of particles and cells -- Joule heating in electrokinetic flow -- Mixing -- Electrokinetic focusing -- Electrokinetic dispensing -- Molecular dynamic simulations -- Other non-continuous approaches -- Electrowetting and droplets -- Nanofluidics -- Flow in channels with 3D elements -- Electrokinetic transport with biochemical reactions -- Photolithography -- Silicon micromachining -- Laser based micromachining -- LIGA -- Soft photolithography -- Nanochannel fabrication -- Molecular tagging method -- Micro PIV -- On-chip waveguide -- Other micro flow visualization techniques -- Fluorescent thermometry -- Electrical current monitoring methods for evaluating EOF velocity -- Methods for measuring zeta potential -- Methods for surface modification (e.g., self assembled monolayer, polymer coating) -- Microfluidic pumping -- Microfluidic mixing -- Microfluidic dispensing -- Microfluidic bioreactors -- Lab-on-chip devices for DNA analysis (e.g., PCR, hybridization, sequencing) -- Lab-on-chip devices for separation based detection (e.g., electrophoresis) -- Lab-on-chip devices for cell analysis (e.g., flow cytometry, dielectrophoresis) -- Lab-on-chip devices based on electro-wetting -- Lab-on-chip devices for protein analysis -- Lab-on-chip devices for immunoassay -- Lab-on-chip devices for chemical analysis -- Lab-on-chip devices for bio-defense applications -- Micro-fuel cells -- Micro heat pipes -- Opto-microfluidics and opto-nanofluidics.
Keywords: Engineering; Medical microbiology; Analytical chemistry; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Biomedical engineering; Nanotechnology; Engineering; Engineering Fluid Dynamics; Nanotechnology; Engineering Thermodynamics, Heat and Mass Transfer; Biomedical Engineering; Analytical Chemistry; Medical Microbiology; Electronic books